Decrease in spermatic parameters of mice treated with hydroalcoholic extract Tropaeolum tuberosum “mashua” - Vásquez, Jonathan H. (2012)
In this work, we provided a Tropaeolum tuberosum hydroalcoholic extract to male mice (780 mg kg-1) for 7, 14 and 21 days treatment, there was no significant difference in body weight gain, testes, epididymides and prostate weight (p> 0.05), nevertheless progressive motility decreased and immobile sperm count increased significantly after 21 days treatment (p <0.05). The sperm count in the epididymis cauda decreased in the 3 three assessments, concentration on 21 days treatment was significantly lower than those of 7 and 14 days treatments (p <0.05). Our results suggest, that T. tuberosum has a direct action on the male reproductive system decreasing spermatic parameters without exerting toxic effects on mice.